Endohedral Metallofullerenes : Basics and Applications - Lu, Xing; Echegoyen, Luis; Balch, Alan L.; Nagase, Shigeru; Akasaka, Takeshi (CRC Press LLC, 2015)
Knowledge on endohedral metallofullerenes (EMFs) has increased dramatically during the last decade. Numerous research findings have been reported, making it an opportune time to provide a systematic update on EMFs. Endohedral Metallofullerenes: Basics and Applications presents the most comprehensive review on all aspects of EMFs including their generation, extraction and isolation, structural issues, theories, intrinsic properties, chemical behaviors, and potential applications. In this book, the editors have collected an impressive amount of information regarding this family of a truly sui ge.